Discourse Analysis in Sitcom Victorious Using Speech Act Theory - Daniela, Lendly (Journal of Linguistic and Literature Studies, 2023)
This research analyzes short conversations taken from the Sitcom Teens series in 2010 entitled Victorious. This research uses speech act theory as the main basis in understanding one of the short scenes in this series. In this case, the author focuses on the three classifications of speech acts expressed by Austin (1962) regarding the three classifications of speech acts, namely locutionary acts, illocutionary acts and perlocutionary acts. The total utterances analyzed were 19 utterances expressed by three actors. The results of this analysis have concluded as a whole the types of illocutionary acts used in the conversation, which have been explained clearly using the Findings column. There are several results from this analysis, there are five locutionary acts and four illocutionary acts in the first scene. Then in the next scene, nine locutionary acts, three illocutionary acts and six perlocutionary acts were found.